2018
DOI: 10.1186/s13046-018-0687-5
|View full text |Cite|
|
Sign up to set email alerts
|

RHBDD1 promotes colorectal cancer metastasis through the Wnt signaling pathway and its downstream target ZEB1

Abstract: Background40–50% of colorectal cancer (CRC) patients develop metastatic disease; the presence of metastasis hinders the effective treatment of cancer through surgery, chemotherapy and radiotherapy, which makes 5-year survival rate extremely low; therefore, studying CRC metastasis is crucial for disease therapy. In the present study, we investigated the role of rhomboid domain containing 1 (RHBDD1) in tumor metastasis of CRC.MethodsThe expression of RHBDD1 was analyzed in 539 colorectal tumor tissues for its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 39 publications
(61 reference statements)
1
52
0
Order By: Relevance
“…β-Catenin is one of the core proteins in the Wnt signaling pathway, and it was shown that phosphorylation at Ser552 and Ser675 of β-catenin could activate the β-catenin mediated signaling pathway. [24][25][26] In this study, in EYA4 overexpressed cells and EYA4 KO cells, the total level of β-catenin and p675-β-catenin did not change, but the level of p552-β-catenin was decreased in EYA4 overexpressed cells and increased in EYA4 KO cells. To investigate whether p552-β-catenin can facilitate transcription of MYCBP, we established β-catenin overexpressed plasmids with (WT) or without S552A mutation, a negative phosphorylated mutation of β-catenin at Ser552.…”
Section: Discussionmentioning
confidence: 49%
“…β-Catenin is one of the core proteins in the Wnt signaling pathway, and it was shown that phosphorylation at Ser552 and Ser675 of β-catenin could activate the β-catenin mediated signaling pathway. [24][25][26] In this study, in EYA4 overexpressed cells and EYA4 KO cells, the total level of β-catenin and p675-β-catenin did not change, but the level of p552-β-catenin was decreased in EYA4 overexpressed cells and increased in EYA4 KO cells. To investigate whether p552-β-catenin can facilitate transcription of MYCBP, we established β-catenin overexpressed plasmids with (WT) or without S552A mutation, a negative phosphorylated mutation of β-catenin at Ser552.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have reported that Capn4 promotes the invasion and metastasis of many cancers by activating the Wnt/β‐catenin signaling pathway . Many studies have also shown that ZEB1 is a downstream target of the Wnt/β‐catenin signaling pathway . Thus, we speculated that Capn4 regulates ZEB1 expression by activating the Wnt/β‐catenin signaling pathway in ESCC cells.…”
Section: Resultsmentioning
confidence: 83%
“…However, while GDNF is mutated in the signaling cascade, it may cause the pathway to be inactive. CARM1 (modified by methylation and phosphorylation) transmits the signal to TF ZEB1, which may be upregulated to cause cell proliferation Zhang et al, 2018). TF ZEB1 plays an important role in this pathway to connect the early-stage and mid-stage of CRC.…”
Section: Genetic and Epigenetic Progression Mechanisms Of Early-stagementioning
confidence: 99%